Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/ac1014386
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Electrospray Ionization Mass Spectrometry Analysis of Water-Soluble Organic Aerosols Collected with a Particle into Liquid Sampler

Abstract: This work demonstrates the utility of a particle-into-liquid sampler (PILS), a technique traditionally used for identification of inorganic ions present in ambient or laboratory aerosols, for the analysis of water-soluble organic aerosol (OA) using high-resolution electrospray ionization mass spectrometry (HR-ESI-MS). Secondary organic aerosol (SOA) was produced from 0.5 ppm mixing ratios of limonene and ozone in a 5 m(3) Teflon chamber. SOA was collected simultaneously using a traditional filter sampler and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 62 publications
4
81
0
Order By: Relevance
“…Compounds were removed from the list if they contained any H : C < 0.5, O : C > 3 or DBE > 20. Using the formulae, the intensity weighted mean O : C and H : C ratios of each sample were determined (Bateman et al, 2010) and these used to calculate the average carbon oxidation state (OS C ) according to Kroll et al (2011).…”
Section: Offline Analysis: Fourier Transform Ion Cyclotron Resonance mentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds were removed from the list if they contained any H : C < 0.5, O : C > 3 or DBE > 20. Using the formulae, the intensity weighted mean O : C and H : C ratios of each sample were determined (Bateman et al, 2010) and these used to calculate the average carbon oxidation state (OS C ) according to Kroll et al (2011).…”
Section: Offline Analysis: Fourier Transform Ion Cyclotron Resonance mentioning
confidence: 99%
“…In this study, we have identified a subset of biogenic VOCs with an aim to represent a broad range of emitted species and the corresponding range in the rates and chemical complexity of their subsequent degradation. Based on the available information on the atmospheric lifetimes of observed biogenic VOCs with respect to reaction with OH radicals and O 3 , and current understanding of their known or probable degradation pathways, it is reasonable to divide the biogenic VOCs into a series of structural subsets possessing similar characteristics (Atkinson and Arey, 2003). As a result, consideration of a single compound from each category provides a reasonable starting point for simplifying the emitted speciation whilst maintaining the range in oxidation timescales and propensities to generate SOA.…”
Section: Rationale Behind the Choice Of Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…www.atmos-chem-phys.net/11/10649/2011/ organic compounds (Bateman et al, 2010). In order to couple the PILS (Brechtel Manufacturing Inc.) to the TOFMS, the use of HPLC pumps in addition to a commonly used peristaltic pump was critical to overcome the backpressure of the TOFMS inlet and to supply steady flow of water (18.2 M , Milli-Q, Millipore) into the boiler.…”
Section: Gas and Particle Analysismentioning
confidence: 99%
“…However, there is no single analytical method to analyze SOA products. In fact, each author develops own analytical methods, according to their needs (Forstner et al, 1997;Yu et al, 1998;Kleindienst et al, 2004;Chiappini et al, 2006;Bateman et al, 2010). Developing an analytical method is complex, long and rarely valued.…”
Section: Introductionmentioning
confidence: 99%